Syndrom krátkého streva - Sýkora, J; Stozický, F; Solc, J; Huml, P; Cerný, V (Ceskoslovenska pediatrie, 1993)
This study was designed to asses the clinical course of five children with a short bowel syndrome after massive intestinal resection during neonatal period. On the basis of their experience the authors analyze some properties that may be advantageous in this syndrome and discuss the most important factors, including enteral feeding at an early postresection stage, which influence a full development of the small bowel adaptive mechanisms. They point out that so called "short gut colitis", sometimes occurring during advancement of enteral nutrition, can be successfully treated by sulphasalazine. The authors come to the conclusion that the prognosis for newborn infants undergoing an excessive bowel resection is far well thanks to enhancement of the intestinal adaptation by a combination of a long-term parenteral nutrition with enteral feeding.
Keywords: Short Bowel Syndrome; kojenec; Female; lidé; novorozenec; syndrom krátkého střeva; Infant, Newborn; Infant; Male; ženské pohlaví; Humans; mužské pohlaví